Sticky Cost Behavior on Cost of Production and Non-Production of Agricultural Sector Companies from 2013-2018 in Indonesia (Evidence from IDX) - Christien, Cinthia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This study aims to provide empirical research related to explain indication of cost stickiness in the cost of production, non-production, and whether there is any difference between those in agricultural companies and the reactions to the volume of activities in agricultural companies by using cost of revenue, selling, general, and administrative cost as proxies in this research and focusing on agricultural sector companies that are listed on Indonesian Stock Exchange from 2013-2018..This study. Data are taken by using criteria (purposive sampling method and analyzed by using multiple linear regression and ABJ model to find the indication of stickiness. The research results show production cost and non production cost are sticky to activity volume and there is significant difference between cost stickiness onÂ  production cost and non-production cost in agricultural sector companies.